Implementation of Salibu Rice Technnology in Supporting Food Security in West Sumatra - Sri Wahyuni (International Journal of Agricultural Sciences, 2020)
This study aims to describe the characteristics of innovation, communication patterns, and sustainability of the application of salibu technology in Tanah Datar District; and to analyze the correlation between innovation characteristics and communication patterns on the sustainability of salibu technology in Tanah Datar. This research was quantitatively using a survey method and supported by qualitative descriptive data. The research location was chosen purposively based on the location topography, that is, in the Tarab River and Batipuh subdistricts. Data analysis is done using descriptive statistical analysis and inferential statistics using the software SPSS 23.00. The characteristics of technological innovation are generally quite good. The pattern of communication is relatively good. The type of communication applied is dialogical by involving the participation of all actors, the direction of communication is convergent, and the frequency and the quality of communication are done where the perpetrators equally understand the meaning of the message conveyed. The adoption in both areas has been sustainable in each harvest season, increased land area, and the desire to continue implementing and developing salibu technology. Sustainability is supported by the characteristics of innovation and communication patterns in both regions.